2015
DOI: 10.17311/sciintl.2015.37.47
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Friendly Weed Control Options for Sustainable Agriculture

Abstract: Background: Weeds are unwanted plants playing a very important role in different eco-systems and many of them cause enormous direct and indirect losses. The losses include interference with cultivation of crops, loss of biodiversity, loss of potentially productive lands, loss of grazing areas and livestock production, erosion following fires in heavily invaded areas, choking of navigational and irrigation canals and reduction of available water in water bodies. Weed management takes away nearly one third of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…When weeds grow contemporaneously with crops, they decrease the productivity of those crops or reduce the quality of the harvested product because of competition for sunlight, water, space, and nutrients [5]. Weeds are regarded as a major pest, which is responsible for 45% of crop yield losses, while 25,20,15, and 6% of yield losses are caused by pathogens, insects, storage pests, and rodents, respectively [6]. Bajwa et al [7] also reported that in the absence of weed control methods, yield losses exceed 70%.…”
Section: Introductionmentioning
confidence: 99%
“…When weeds grow contemporaneously with crops, they decrease the productivity of those crops or reduce the quality of the harvested product because of competition for sunlight, water, space, and nutrients [5]. Weeds are regarded as a major pest, which is responsible for 45% of crop yield losses, while 25,20,15, and 6% of yield losses are caused by pathogens, insects, storage pests, and rodents, respectively [6]. Bajwa et al [7] also reported that in the absence of weed control methods, yield losses exceed 70%.…”
Section: Introductionmentioning
confidence: 99%
“…Allelopathy is a biological phenomenon caused by the release of plant-produced toxins or stimuli (allelochemicals) from aerial parts into the phyllosphere or from underground parts into the rhizosphere to influence the growth, survival, or reproduction of other organisms [2]. The search for environmental friendly and economical weed control options has increased the quest for exploring the allelopathic phenomenon by using allelochemicals as bio herbicides in agricultural systems [3,4,5]. Similarly, interest in the use of natural phytochemicals as a resource for developing pharmaceutical and agricultural products has increased dramatically in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of red clover mass improved the nutrition and weed-competitiveness of cereals. This practice is widely used in other countries [15]. A significantly Table 5 The effect of perennial forage legumes and their above-ground biomass management methods on the weed density and dry weight, Experiment II lower dry weight of weeds (45% lower) was observed in the experiment that used fermented pea and spring wheat mass.…”
Section: Spring Wheatmentioning
confidence: 97%